Rice response to spermine foliar application and its association with aerial imagery monitoring under water stress conditions - Nur Zahirah Abd. Jalil,; Zulkarami Berahim,; Nurul-Idayu Zakaria,; Mohamad Husni Omar,; Rhushalshafira Rosle,; Mohd Razi Ismail,; Nik Norasma Che´Ya,; Anas Abdul Latiff,; Wan Fazilah Fazlil Ilahi,; Gandjaeva, Lola (Penerbit Universiti Kebangsaan Malaysia, 2024)
Rice is the most consumed food in the world, mainly in Asia and Africa. Malaysia is the second-largest rice importer in Southeast Asia after Indonesia. However, rice yield is limited by water stress. One alternative for a quicker strategy to mitigate water stress is through a combination of foliar spermine application and efficient rice management practices via image monitoring techniques using drone technology. The present study was aimed at evaluating the effects of spermine on rice physiological response and its association with aerial imagery and yield during reproductive stage under water stress. The experiment was carried out under greenhouse conditions using a two-factorial randomized complete block design (RCBD), with foliar spermine treatment as the first factor and water stress as the second factor. Physiological parameters showed significantly higher tiller number per pot and photosynthesis rate by 29% and 31%, respectively. Correspondingly, the Normalised Difference Vegetation Index (NDVI) using aerial imagery monitoring showed an increased value in spermine treatments by 2% compared to control. Furthermore, NDVI readings and photosynthetic rate were positively correlated linearly with R2 = 0.51. Interestingly, spermine treatments alleviated water stress effects by 40%, 17% and 12% in grain weight per pot, grain number per panicle and percentage filled grain. Biomass partitioning in roots improved by 44% in spermine treatments, even under water stress, due to an efficient translocation of assimilates. In conclusion, spermine foliar application significantly improved growth, grain filling and rice yield production, which was also supported by NDVI values using aerial imagery monitoring.